Enhancing Surgical Outcomes: Evaluating the Impact of Implementing the World Health Organization Surgical Safety Checklist—A Prospective Cross-Sectional Study - Gasoma, ElMuhtadi B. Y.; Marouf, Mohamed A. (The Surgery Journal, 2024)
Background Globally, surgical care plays a vital role in health care. Unfortunately, complications arise in approximately 5 to 18% of surgical procedures. However, research has shown that following the surgical safety checklist provided by the World Health Organization (WHO) can significantly reduce these complications and surgery-related fatalities. The objective of this study was to assess the accuracy and completion of the WHO Surgical Safety Checklist.Materials and Method From October 3, 2022 to February 28, 2023, a comprehensive observational study was conducted involving 300 patients who underwent elective and emergency surgeries. The completion rates for the different stages of surgery, namely sign-in, time-out, and sign-out, were determined using the SPSS 22.0 software.Result In our research, we specifically examined the completion of the checklist for 300 patients who underwent important procedures within a span of 5 months. For each patient, we ensured that their identities, procedures, and consent were verified with a 100% success rate. Additionally, we thoroughly checked the anesthesia equipment and drugs for safety in every case. Furthermore, all essential images were consistently displayed for each patient, achieving a 100% adherence to this crucial aspect of the process.Conclusion In general, the level of completeness of the checklist was satisfactory across the sign-in, time-out, and sign-out phases. While this study did not assess the specific outcomes, it is presumed that incomplete data may have exposed patients to potential perioperative complications.
Keywords: surgical safety checklist; surgical complications; sign in; time out; sign out